Drip Irrigation in Castor Enhances Bean Yield, Saves Water and Increases Profitability - Rao, V. Praveen; Suresh, G.; Ramanjaneyulu, A. V.; Anitha, V. (Chronicle of Bioresource Management, 2023)
The castor growers are compelled to obtain low yields (500-600 kg ha-1) and returns leading to crop shift due to various abiotic and biotic stresses in rainfed castor. But there is a dire need to enhance castor yields as the global castor oil market is expected to touch $1,470 million by the end of 2025 due to its wide-ranging applications in the specialty chemical industry. We found that growing castor in winter season combined with drip irrigation and fertigation presents an excellent opportunity for enhancing bean yield, profits and saving scarce water resources. The discounted cash flow analysis suggested that, the investment on drip system in castor can be recovered in an year (two crop seasons without any subsidy). The PMKSY (Pradhan Mantri Krsihi Sinchayee Yojana) at country level and subsidies between 50 to 90% in Telangana State may encourage farmers in largescale adoption of drip irrigation in castor.